Eastern-country-stydy-tour (Dong du) movement in the revolutionary prosess of Vietnam nationl liberation and in cultural, educationa relations between Vietnam and Japan - Khanh, Nguyen Van; Suu, Nguyen Van (VNU Journal of Science: Social Sciences and Humanities, 2005)
Abstract